The effect of biochar on the physiological, morphological and anatomical characteristics of mung bean roots after exposure to salt stress - Nikpour-Rashidabad, Neda; Tavasolee, Alireza; Torabian, Shahram; Farhangi-Abriz, Salar (Archives of Biological Sciences, 2019)
Paper description: Previous reports showed that biochar alleviates salt toxicity in different crops. In the current study, we explain the effects of biochar on root anatomy and morphology of mung bean plants, which has not been evaluated so far. Biochar, by changing root anatomy and increasing the indole-3-acetic acid content improves mung bean performance under salt stress. Abstract: To investigate the changes in the anatomical and physiological characteristics of mung bean roots in response to biochar treatment during salt stress, a pot experiment was conducted. Mung bean plants were subjected to three biochar concentrations (0, 50 and 100 g kg-1 soil) and three salinity treatments (0, 5 and 10 dSm-1 NaCl). Salinity decreased root growth, vascular cylinder (VC) and cortical parenchyma (CP) areas, affecting the VC/CP ratio, shoot dry weight, the relative water content (RWC) of roots and leaves, and the root indole-3-acetic acid (IAA) content. It increased specific root length, the shoot/root ratio and root abscisic acid (ABA), and 1-aminocyclopropane-1-carboxylic acid (ACC) contents. Plant growth, RWC, the shoot/root ratio, specific root length, total root area, VC and CP areas, and the IAA/ABA and IAA/ACC ratios were increased by biochar under saline media. Biochar improved xylem structure, the plant growth regulator IAA, and decreased stress hormones, ABA and ACC, which accelerate plant senescence, consequently increasing mung bean growth under salt stress. https://doi.org/10.2298/ABS181005014N Received: October 5, 2018; Revised: March 5, 2019; Accepted: March 12, 2019; Published online: March 18, 2019 How to cite this article: Nikpour-Rashidabad N, Tavasolee A, Torabian S, Farhangi-Abriz S. The effect of biochar on the physiological, morphological and anatomical characteristics of mung bean roots after exposure to salt stress. Arch Biol Sci. 2019;71(2):321-7.